2018
DOI: 10.1038/s41386-018-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of dopamine, but not norepinephrine, in the sex-specific regulation of juvenile socially rewarding behavior by vasopressin

Abstract: Social play is a highly rewarding behavior displayed mostly during the juvenile period. We recently showed that vasopressin V1a receptor (V1aR) blockade in the lateral septum (LS) enhances social play in male juvenile rats, but reduces it in females. Here, we determined whether the LS-AVP system modulates dopamine (DA) and/or norepinephrine (NE) neurotransmission in the LS to regulate social play behavior in sex-specific ways. Using microdialysis combined with retrodialysis, we demonstrated that both LS-AVP ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 42 publications
2
12
1
Order By: Relevance
“…AVP fiber density in the LS is significantly higher in male than in female rats, 51 and female rats show higher V 1A binding density than males. 52 Also, Bredewold and colleagues 20 showed that manipulation of the AVP system in the LS is associated with sex-specific responses in social play behavior, a natural reward. In addition, different responses in AVP LS content were observed in male and female rats after acute AMPH administration.…”
Section: Discussionmentioning
confidence: 99%
“…AVP fiber density in the LS is significantly higher in male than in female rats, 51 and female rats show higher V 1A binding density than males. 52 Also, Bredewold and colleagues 20 showed that manipulation of the AVP system in the LS is associated with sex-specific responses in social play behavior, a natural reward. In addition, different responses in AVP LS content were observed in male and female rats after acute AMPH administration.…”
Section: Discussionmentioning
confidence: 99%
“…One possible site of OT-V1aR cross-talk is the lateral septum (LS). The dorsal LS has V1aR expression and abundant AVP and OT fibers (68), and V1aR modulate social play behavior by inducing dopamine release (69). Ventral LS has strong OTR expression as well as AVP and OT fibers (68).…”
Section: Oxytocin In Vta and Nac Facilitates Social Approachmentioning
confidence: 99%
“…Lastly, while sex differences in the current set of behavioral experiments were minimal, we would encourage the continued use of both sexes in future investigations of the neural substrates underlying social versus food preference [52,53]. This is critical because an absence of sex differences in behavior could still be caused by sex differences in its neural underpinnings [54], and we and others have demonstrated that the neural mechanisms underlying motivated social behavior can differ in males and females [34,[55][56][57][58][59][60].…”
Section: The Social Versus Food Preference Test Is a Flexible Behavmentioning
confidence: 91%